“Korona” is the new adaptable winter bread wheat variety for the North-Caucasus region - N. A. Morozov; V. V. Ivanov; I. V. Samsonov (Зерновое хозяйство России, 2020)
Wheat is one of the main crops that ensure the country's food security and export potential. In the Stavropol Area winter wheat annually occupies more than 1.5 million hectares. Despite this, grain productivity and quality remain unstable. To increase the volume of grain production in the country and improve its quality, the development and rapid introduction of new varieties into production is of fundamental importance. The purpose of the current study was to develop a new winter bread wheat variety adaptable to the sharply continental climate of the North Caucasus region, with a high level of productivity and grain quality. According to the positive results of the trials in the North Caucasus region, since 2019 the new winter bread wheat variety “Korona”, developed by the FSEP “Prikumskaya Experimental Breeding Station”, has been included in the State List of Breeding Achievements and recommended for cultivation. The variety was developed by the method of complex staged hybridization with the participation of the best local lines “126768”, “140356” (FSEP “Prikumskaya Experimental Breeding Station”) and the varieties “Don 95” (FSBSI “ARC “Donskoy”), “Ukrainka Odesskaya” (Ukraine). Over the years of the State Variety Testing (2017-2018) at the variety plots of the Stavropol Area, the variety ‘Korona' has shown a significant productivity advantage over the standard variety “Grom” in extremely arid and arid zones, with an increase of 0.40 and 0.39 t/ha, respectively. During the years of study, the maximum productivity (11.71 t/ha) was obtained at the Stavropol SVTS. When testing the variety in the Republics of the North Caucasus, the maximum productivity increases to the standard varieties were obtained in Adygea (+0.46 t/ha), Karachay-Cherkessia (+ 0.65 t/ha), Crimea (+0.42 t/ha). According to the FSEP “Prikumskaya Experimental Breeding Station”, the new variety “Korona” has formed large-sized well-made grain with high baking qualities. The yield of bread from flour of a new genotype exceeded the standard and was 638 ml, the general estimation of bread was 4.8 points. The variety belongs to the valuable wheat varieties. The grain of the new variety contains on average 13.4% of protein, 26.4% of gluten of the first quality group, 75 of IDK. In 2019, for large productivity and environmental adaptability the new variety “Korona” was awarded a diploma of the State Variety Commission of the Russian Federation and was awarded the title “The Variety of the Year”.